Understanding the impact of 'wish-granting' interventions on the health and well-being of children with life-threatening health conditions and their families: A systematic review. (September 2022) - Heath, Gemma; Screti, Cassandra; Pattison, Helen; Knibb, Rebecca
This review aimed to explore how wish-granting interventions impact on the health and well-being of children with life-threatening health conditions and their families, using any study design. Six electronic databases (Medline; PsycINFO; CINAHL; Embase; AMED and HMIC) were systematically searched to identify eligible research articles. Studies were critically appraised using a Mixed Methods Appraisal Tool. Findings were synthesized narratively. 10 papers were included, reporting studies conducted across five countries, published from 2007 to 2019. Study designs were diverse (four quantitative; two qualitative and four mixed method). Results indicated improvements to physical and mental health, quality of life, social well-being, resilience and coping for wish children, parents and siblings. In conclusion, wish-granting interventions can positively impact health and therefore should not be discouraged; however, more research is needed to define and quantify the impact of wish fulfilment and to understand how it can be maximized.